Meaning in Life : An Analytic Study - Metz, Thaddeus (UK Oxford Oxford University Press, 2014)
What makes a person's life meaningful? Thaddeus Metz argues that no existing theory does full justice to the key requirements of morality, enquiry, and creativity. He offers a new answer to the question: meaning in life is a matter of intelligence contoured toward fundamental conditions of human existence
Include Bibliography and Index
Keywords: Life -- Meaning (Philosophy) -- Spirituality